Multi-functional role of apolipoprotein E in neurodegenerative diseases - Islam, Sadequl; Noorani, Arshad; Sun, Yang; Michikawa, Makoto; Zou, Kun (Frontiers in Aging Neuroscience, 2025)
Genetic diversity in the apolipoprotein E (ApoE) gene has been identified as the major susceptibility genetic risk factor for sporadic Alzheimer’s disease (SAD). Specifically, the ApoEε4 allele is a significant risk factor for SAD, while ApoEε2 allele provides protection compared to the more common ApoEε3 allele. This review discusses the role of the ApoE in AD and other neurodegenerative disorders. ApoE, a cholesterol transport protein, influences several pathways involved in neurodegeneration, particularly in AD. Beyond its established role in amyloid β-protein (Aβ) metabolism and deposition, ApoE also impacts tau pathology, neurodegeneration, and the microglial response to AD. The review aims to provide an updated overview of ApoE’s diverse roles, emphasizing its involvement in Aβ clearance through ApoE receptors. It also covers ApoE’s influence in other neurodegenerative diseases like Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), Huntington’s disease (HD), vascular dementia (VD), and multiple sclerosis (MS). New research highlights the interaction between ApoE and presenilin (PS), suggesting connections between familial AD (FAD) and SAD. The review also explores protective effects of ApoE mutations against AD and ApoE4-induced tauopathy, neurodegeneration, and neuroinflammation. The insights from this comprehensive update could indeed lead to new therapeutic strategies for neurodegenerative diseases.